Provinciale Dienst voor Cultuur - Jaarverslag 1974. - Provincie West-Vlaanderen (Brugge : Provinciale Dienst voor Cultuur, 1976)
Decroubele, Luc ; Verduyn, Jacques ; Vandekerckhhove, Rita ; De Pauw, Claudine ; Mara, Pol ; etc.
Nederlands
boek